prove true or false,if false, correct it

Asked by suryap2 | 2nd Oct, 2010, 01:53: PM

Expert Answer:

Dear Student,
 
This is True.
Explanation:
Substituting y/sina = bx/acosA (from first equation) in the second equation, we get:
     a2x/acosA - b2/acosA = a2 - b2
=> (a2 - b2)x/acosA = a2 - b2
=> x/acosA = 1................................. (IF a is NOT equal to b)
=> x = acosA
=> y = bsinA
Substituting these values in the given expression (the third one), we get
cos2A + sin2A = 1.... which is true
 
Regards Topperlearning.

Answered by  | 3rd Oct, 2010, 11:47: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.